Analyzing Strategic Intuition Capability Among Sabu Raijua Entrepreneurs: The Role of Managerial Cognitive Capability and Absorptive Capacity - Suprapto , Widjojo; Harjanti, Dhyah; Praptiningsih, Maria; Johannes, Joy (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Entrepreneurs need strategic intuition capability in dealing with business situations that are constantly evolving, dynamic, and uncertain. This study was conducted to determine how the influence of managerial cognitive capabilities and absorptive capacity on strategic intuition capability among entrepreneurs in Sabu Raijua Regency. Design/methodology/approach: The nature of this study is explanatory with a quantitative approach. There were 105 respondents who took part in filling out the online questionnaire. The collected data were later processed with the Smart PLS 4.0 software. Research Findings: This study proves that managerial cognitive capability has a significant impact on strategic intuition capability, managerial cognitive capability has a significant impact on absorptive capacity, but absorptive capacity has no effect on strategic intuition capability. Theoretical Contribution/Originality: This research makes a number of theoretical contributions, particularly with regard to the relationship between managerial cognitive capabilities, absorptive capacity, and strategic intuition capability. The managerial implications of this research are useful for entrepreneurs in evaluating or improving themselves in order to continue to develop the business being managed.